2019
DOI: 10.1002/aoc.5191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of titanium nanoparticles using Allium eriophyllum Boiss aqueous extract by green synthesis method and evaluation of their remedial properties

Abstract: The application of nanotechnologies to medicine, or nanomedicine, which has already demonstrated its tremendous impact on the pharmaceutical and biotechnology industries, is rapidly becoming a major driving force behind ongoing developments in the antimicrobial and wound healing fields. This study confirms the potential of Allium eriophyllum Boiss aqueous extract for the green synthesis of titanium nanoparticles (TiNPs). Also, we reveal the antioxidant, cytotoxicity, cutaneous wound healing, antifungal and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Among the phytosynthesized TiO 2 NPs, kola seed mediated particles were the most potent, while the least activities were obtained for KSS-TiO 2 NPs having highest performance of 52.37%. Authors have reported DPPH scavenging activities of 2–85% for TiO 2 NPs biosynthesized using plants such as Psidium guajava, Pithecellobium dulce, Lagenaria siceraria, Allium eriophyllum and Artemisia haussknechtii [ 60 , 68 , 69 , 70 ] at concentrations ranging from 1-1000 μg/ml. The present report proves that TiO 2 NPs produced using kola extracts can attack disease-causing free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Among the phytosynthesized TiO 2 NPs, kola seed mediated particles were the most potent, while the least activities were obtained for KSS-TiO 2 NPs having highest performance of 52.37%. Authors have reported DPPH scavenging activities of 2–85% for TiO 2 NPs biosynthesized using plants such as Psidium guajava, Pithecellobium dulce, Lagenaria siceraria, Allium eriophyllum and Artemisia haussknechtii [ 60 , 68 , 69 , 70 ] at concentrations ranging from 1-1000 μg/ml. The present report proves that TiO 2 NPs produced using kola extracts can attack disease-causing free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…In our opinion, the effect could have been influenced by the presence of multiple morphologies in the larger particles case. Other, more exotic metallic nanoparticles (Ti NPs and Se NPs) were obtained by Seydi et al [57] and Gunti et al [58], respectively, by using aqueous extracts that were obtained from different plants. In both cases, the NPs were spherical, with dimensions of 22 and 15-40 nm, respectively, and they were effective against several Gram-positive bacteria, Gram-negative bacteria, and fungal lines, with MBC/MFC values close to the positive controls (commercial antimicrobials) for Ti NPs [57].…”
Section: Au Npsmentioning
confidence: 99%
“…Nanoparticles of a wide range of elements such as copper (Cu) [ 16 ], gold (Au) [ 17 ], silver (Ag) [ 18 ], titanium (Ti) [ 19 ], zinc (Zn) [ 20 ], silicon (Si) [ 21 ] and palladium (Pd) [ 22 ] and their oxides are abound in literature. Specifically, copper is a good conductor of heat or electricity and it is cheaper than silver and gold [ 23 ].…”
Section: Introductionmentioning
confidence: 99%